1972
DOI: 10.1063/1.1660809
|View full text |Cite
|
Sign up to set email alerts
|

dc and ac Josephson Effect in Sputtered Nb–NbOx–Pb Junctions

Abstract: The magnetic field dependence of the maximum dc Josephson current and of the ac Josephson-effect-induced step structure have been measured for sputtered Nb–NbOx–Pb Josephson junctions, and found to be in very good agreement with theoretical predictions; even for junctions made with ``dirty'' Nb thin films. From this agreement it is concluded that the observed anomalies in the I-V characteristics, namely, excess currents for voltages Δ(Pb)<V<Δ(Pb) + Δ(Nb) and a ``knee'' in the I-V curve at voltage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1973
1973
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The relation between the effective A, and the penetration depth in the case of finite thickness of the electrode is given by [23] A, = A t m h ($-) with d as the thickness of the sitperconducting electrode. I n the case of 3, > d the effective penetration depth is limited by the value Ae = d / 2 .…”
Section: Penetration Depth Of Magnotic Field In Vanadium Filmsmentioning
confidence: 99%
“…The relation between the effective A, and the penetration depth in the case of finite thickness of the electrode is given by [23] A, = A t m h ($-) with d as the thickness of the sitperconducting electrode. I n the case of 3, > d the effective penetration depth is limited by the value Ae = d / 2 .…”
Section: Penetration Depth Of Magnotic Field In Vanadium Filmsmentioning
confidence: 99%
“…We mean the so-called knee, a sudden current decrease in low-temperature I - V characteristics of Nb-based S-I-S junctions at voltages slightly just above a strong increase of the current that was expected to occur at the sum of V Δ values for the two superconducting electrodes [ 4 ] (see also [ 5 ]). Moreover, the current values at very low temperatures and at voltages lower than the sum of V Δ were considerably larger than theoretically anticipated for the BCS densities of states [ 6 ]. Later, it was shown experimentally that this anomaly may be caused by the presence of a normal conducting layer on the superconducting niobium film [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the current values at very low temperatures and at voltages lower than the sum of V Δ were considerably larger than theoretically anticipated for the BCS densities of states [ 6 ]. Later, it was shown experimentally that this anomaly may be caused by the presence of a normal conducting layer on the superconducting niobium film [ 6 , 7 ]. This statement was confirmed theoretically [ 8 ] in the framework of the proximity-effect model which treats incoherent single-particle scatterings from a normal layer to a superconducting one within a tunnel-barrier approximation [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Secondly there is a negative resistance region in the vicinity of LI Nb + d Pb. Both anomalies are commonly seen in Nb junctions qualitative explanations involving proximity effect and gaplessness having been offered [10], [11 ]. 4 and, as can be seen it has a higher value of Y2 and a leakage at least as small as the best film devices.…”
mentioning
confidence: 81%
“…The Josephson effect. -Although the quasiparticle tunneling characteristics of Nb based tunnel junctions are not ideal, Schwidtal [10] has shown that nearly ideal Josephson tunneling behavior is possible. As is evident from figure 2, our wire junctions exhibit TABLE 1 large critical currents which are quite repeatable from junction to junction.…”
mentioning
confidence: 99%